2019
DOI: 10.1108/jeee-09-2018-0091
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of Indian student attitudes towards entrepreneurs and managers

Abstract: Purpose The purpose of this study was to investigate the perceptions of business students in India toward business managers (not self-employed) and entrepreneurs. Design/methodology/approach Students’ perceptions of the ethical behaviors of business managers and entrepreneurs were measured using the Bucar and Hisrich (2001) model. The scale comprises 20 behavioral descriptors, and the students were asked to indicate the degree to which they believed entrepreneurs and business managers would consider these ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Further, they acknowledge that attitudes tend to change over the long run circumstances through an intelligent transform with the environment which is proven by the changing of entrepreneurial attitude of university students are much higher compare to community college peers. Their finding is also supported by various studies (Nguyen, Dinh, Luu, and Choo, 2020;Barber III, Ghouse, Batchelor, Chaher, Harris, and Gibson, 2019;Aloulou, 2016). In addition, according to Robinson, Stimpson, Huefner, and Hunt (1991), entrepreneurial attitudes are the changing of thoughts, feelings, and behavioural intentions related to innovation, achievement, self-esteem, and personal control.…”
Section: Change In Entrepreneurial Attitudesmentioning
confidence: 71%
“…Further, they acknowledge that attitudes tend to change over the long run circumstances through an intelligent transform with the environment which is proven by the changing of entrepreneurial attitude of university students are much higher compare to community college peers. Their finding is also supported by various studies (Nguyen, Dinh, Luu, and Choo, 2020;Barber III, Ghouse, Batchelor, Chaher, Harris, and Gibson, 2019;Aloulou, 2016). In addition, according to Robinson, Stimpson, Huefner, and Hunt (1991), entrepreneurial attitudes are the changing of thoughts, feelings, and behavioural intentions related to innovation, achievement, self-esteem, and personal control.…”
Section: Change In Entrepreneurial Attitudesmentioning
confidence: 71%
“…A study in the United States (Batchelor et al, 2011), found there was a different perception of managers than entrepreneurs. A study using the same methodology on the perceptions of Omani students found no difference between the ethics of managers and entrepreneurs (Ghouse et al, 2019). Hypotheses 2 and 3 were related to the potential difference between American and Czech students' perceptions of managers and entrepreneurs.…”
Section: Resultsmentioning
confidence: 87%
“…Interestingly, except for slight gender differences, Czech student perceptions are similar to those in the United States. Previous research in India (Barber III et al, 2019) showed substantial differences in the perceptions of Indian and U.S. business students. With the U.S. sample viewing both entrepreneurs and managers as more ethical than their Indian counterparts.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 90%
See 2 more Smart Citations